Solvent-modulated proton-coupled electron transfer in an iridium complex with an ESIPT ligand. Issue 13 (10th March 2022) - Kim, Siin; Choi, Jungkweon; Cho, Dae Won; Ahn, Mina; Eom, Seunghwan; Kim, Jungmin; Wee, Kyung-Ryang; Ihee, Hyotcherl
Abstract : The iridium complex with an ESIPT ligand shows solvent-modulated proton-coupled electron transfer, in which the temporal order of proton transfer and charge transfer is altered by the solvent environment. Abstract : Proton-coupled electron transfer (PCET), an essential process in nature with a well-known example of photosynthesis, has recently been employed in metal complexes to improve the energy conversion efficiency; however, a profound understanding of the mechanism of PCET in metal complexes is still lacking. In this study, we synthesized cyclometalated Ir complexes strategically designed to exploit the excited-state intramolecular proton transfer (ESIPT) of the ancillary ligand and studied their photoinduced PCET in both aprotic and protic solvent environments using femtosecond transient absorption spectroscopy and density functional theory (DFT) and time-dependent DFT calculations. The data reveal solvent-modulated PCET, where charge transfer follows proton transfer in an aprotic solvent and the temporal order of charge transfer and proton transfer is reversed in a protic solvent. In the former case, ESIPT from the enol form to the keto form, which precedes the charge transfer from Ir to the ESIPT ligand, improves the efficiency of metal-to-ligand charge transfer. This finding demonstrates the potential to control the PCET reaction in the desired direction and the efficiency of charge transfer by simply perturbing the external hydrogen-bonding network with the solvent.